2020
DOI: 10.1016/j.jqsrt.2020.107169
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of engineering gas radiative property models in high pressure turbulent jet diffusion flames

Abstract: This article aims to determine the most relevant engineering global method for gas radiative property modeling to be applied in the simulations of combustion problems. Two versions of the full-spectrum correlated k (FSCK) model, the Rank-Correlated full-spectrum k-distribution/ Spectral-Line-Weighted-sum-of-gray-gases (RC-FSK/RC-SLW) and a new version of the Weighted-Sum-of-Grey-Gases (WSGG) model are compared with the Narrow-Band CK (NBCK) model in four turbulent axisymmetric jet diffusion flames fueled eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Summary of spectral models. A review of the recent literature reveals that the FSK and SLW models are two of the most popular models for modeling nongray radiation in combustion environments [3,152]. In a recent article [149], it has been shown that the SLW and FSK models share many commonalities.…”
Section: Spectral-line-based Weighted-sum-of-gray-gases (Slw)mentioning
confidence: 99%
See 3 more Smart Citations
“…Summary of spectral models. A review of the recent literature reveals that the FSK and SLW models are two of the most popular models for modeling nongray radiation in combustion environments [3,152]. In a recent article [149], it has been shown that the SLW and FSK models share many commonalities.…”
Section: Spectral-line-based Weighted-sum-of-gray-gases (Slw)mentioning
confidence: 99%
“…Although these two models are frontrunners, the WSGG model continues to be quite popular with its many recent improvements and updates, especially for coal combustion and other applications involving soot and/or high pressure [116,118,119]. Another model that has found some use is the narrow-bandbased k-distribution model or NBCK [152][153][154]. NBCK is computationally far more (>20×) expensive than either FSK or SLW, but has the best accuracy among all methods.…”
Section: Spectral-line-based Weighted-sum-of-gray-gases (Slw)mentioning
confidence: 99%
See 2 more Smart Citations
“…In past years, new developments of the model have relaxed some of its limitations, such as application to gas mixtures with varying molar concentration ratios and non-atmospheric pressures [17] and non-gray boundaries [18]. As shown in a recent study on coupled combustion calculations [19], in comparison with more advanced global gas model, such as SLW/FSCK, the model can provide comparable accuracy, even if not being the most accurate, with less computation time.…”
mentioning
confidence: 99%